Determination of neonicotinoids and 199 other pesticide residues in honey by liquid and gas chromatography coupled with tandem mass spectrometry. (1st June 2019) - Gaweł, Marta; Kiljanek, Tomasz; Niewiadowska, Alicja; Semeniuk, Stanisław; Goliszek, Milena; Burek, Olga; Posyniak, Andrzej
Graphical abstract: Highlights: Simultaneous analysis of 207 pesticides in honey by optimised and validated method. Investigation of pesticide residues of 3-year monitoring of Polish honey samples. About 85% of honey samples contaminated with at least one pesticide residue. Cyano-substituted neonicotinoids were the most frequently detected pesticides in honey. Triazole fungicides were the most numerous group of pesticides detected in honey. Abstract: Current work presents a modified QuEChERS method for the determination of 207 pesticide residues in honey by LC–MS/MS and GC–MS/MS. Acetate buffered acetonitrile extraction with Z-Sep+ and PSA dispersive-SPE clean-up were used for sample preparation. Optimised conditions allows determination of neonicotinoids as well as other insecticides, fungicides, herbicides, acaricides, growth regulators and veterinary drugs in honey samples. Validated method enable sensitive analysis at least at concentrations from 0.001, 0.005 or 0.01 mg/kg for 45%, 41% and 14% of pesticides, respectively. Method was utilised for the analysis of 155 honey samples from Poland during 2015–2017. Residues of 21 pesticides were determined in honey. Cyano-substituted neonicotinoids (acetamiprid, thiacloprid) were quantified in 77% of samples and were the most frequently detected pesticides. Concentrations of acetamiprid was from 0.001 to 0.13 mg/kg whilst thiacloprid from 0.001 to 0.2 mg/kg. Fungicides were determined in 50% and amitraz metabolites in 35% of honey samples.